2017
DOI: 10.18433/j3w31f
|View full text |Cite
|
Sign up to set email alerts
|

Beta Adrenoceptor Polymorphism and Clinical Response to Sertraline in Major Depressive Patients

Abstract: -Purpose: The adrenoceptor family, as one of the main contributors in regulating the noradrenergic system, has been studied in involvement of depression and its treatment. A functional polymorphism of G1165C on beta adrenoceptor (βAR) enhances post receptor signalling and is assumed to be involved in pharmacotherapy of depression. The aim of the present study was to discern the influence of G1165C polymorphism in the β1AR gene on individual differences in response to sertraline. Methods: One hundred newly diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 43 publications
(48 reference statements)
0
6
2
1
Order By: Relevance
“…A study by Crowley et al showed lack of association between the functional polymorphism of G1165C and response to citalopram in depressed patients [28]. Another study carried out by Firouzabadi et al examining the effect of the same polymorphism in response to sertraline suggested that the patients who carried CC genotype responded five times more to sertraline in comparison with other variants and carriers of C allele responded three times more to sertraline than patients with the G allele [29]. According to our knowledge, role of G1165C polymorphism in efficacy of response to fluoxetine in a set of newly diagnosed Iranian MDD patients has not been conducted to date.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Crowley et al showed lack of association between the functional polymorphism of G1165C and response to citalopram in depressed patients [28]. Another study carried out by Firouzabadi et al examining the effect of the same polymorphism in response to sertraline suggested that the patients who carried CC genotype responded five times more to sertraline in comparison with other variants and carriers of C allele responded three times more to sertraline than patients with the G allele [29]. According to our knowledge, role of G1165C polymorphism in efficacy of response to fluoxetine in a set of newly diagnosed Iranian MDD patients has not been conducted to date.…”
Section: Discussionmentioning
confidence: 99%
“…As a means of targeted treatment and personalized medicine, pharmacogenetics has currently drawn a lot of attention in many neurologic and psychiatric diseases (36)(37)(38)(39)(40). Although many studies have focused on the contribution of genetic factors in autism (41,42), their role as therapeutic elements stays illusive.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic variation of beta-1 adrenoceptors might influence clinical response to a specific antidepressant. A clinical study discerned the influence of the G1165C polymorphism in the beta-1 adrenoceptor gene on individual differences in response to sertraline, and it was found that CC genotype-carrying individuals responded five times more to sertraline compared to other variants and that the C allele carriers responded three times more to sertraline than patients with the G allele [ 63 ]. Interestingly, the antidepressant-promoting effect of polymorphism in the beta-1 adrenoceptor gene was not observed in patients who received repeated treatment with fluoxetine, one of the most frequently prescribed antidepressants [ 64 ].…”
Section: Functional Role Of Beta-adrenergic Receptors In Depression A...mentioning
confidence: 99%